2019
DOI: 10.1039/c9md00112c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antitumor activity of aza-brazilan derivatives containing imidazolium salt pharmacophores

Abstract: A series of novel aza-brazilan derivatives containing imidazolium salt pharmacophores were synthesized and their antitumor structure–activity relationship studies were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The introduction of electron-withdrawing groups on the aza-brazilin nucleus produced more active derivatives. Derivatives having an alkyl chain as linker groups produce higher potency as compared to acyl chains [31]. Zhou et al also used a hybrid molecular strategy to conjugate N-substituted tetrahydro-β-carbolines with imidazolium salts.…”
Section: Hybrid Molecules Containing Benzimidazolium Saltsmentioning
confidence: 99%
“…The introduction of electron-withdrawing groups on the aza-brazilin nucleus produced more active derivatives. Derivatives having an alkyl chain as linker groups produce higher potency as compared to acyl chains [31]. Zhou et al also used a hybrid molecular strategy to conjugate N-substituted tetrahydro-β-carbolines with imidazolium salts.…”
Section: Hybrid Molecules Containing Benzimidazolium Saltsmentioning
confidence: 99%
“…In this context, our group has devoted to the synthesis of novel imidazolium salt derivatives and found a series of promising compounds with antitumor activity (Chen et al, 2013;Wang et al, 2013;Xu et al, 2014b;Xu et al, 2015;Zhou et al, 2016a;Zhou et al, 2016b). Further mechanistic studies confirmed that these imidazolium salt derivatives can induce cell cycle arrest and apoptosis in tumor cells (Liu et al, 2013;Liu et al, 2015;Huang et al, 2019). The representative examples are an effective antitumor active diosgenin-imidazolium salt and a new mTOR pathway inhibitor B591 (Figure 1) (Deng et al, 2019;Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our research group has reported a series of works on the design, synthesis, and antitumor activity of imidazole salt compounds. [ 11–24 ] One of the most representative compounds is the imidazolium salt NIBI (Figure 1) which presents powerful in vitro and in vivo antitumor activity, and this study result is a hallmark of our group's breakthrough in this field. [ 25 ] We also studied the antitumor mechanism of some imidazolium salts derivatives, the results showed that they can induce cell cycle arrest and apoptosis of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] We also studied the antitumor mechanism of some imidazolium salts derivatives, the results showed that they can induce cell cycle arrest and apoptosis of tumor cells. [ 13–15 ]…”
Section: Introductionmentioning
confidence: 99%